2002
DOI: 10.1093/jxb/erf091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar UV-B radiation on canopy structure of Ulva communities from southern Spain

Abstract: Within the sheltered creeks of Cádiz bay, Ulva thalli form extended mat-like canopies. The effect of solar ultraviolet radiation on photosynthetic activity, the composition of photosynthetic and xanthophyll cycle pigments, and the amount of RubisCO, chaperonin 60 (CPN 60), and the induction of DNA damage in Ulva aff. rotundata Bliding from southern Spain was assessed in the field. Samples collected from the natural community were covered by screening filters, generating different radiation conditions. During d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 43 publications
(44 reference statements)
3
73
0
4
Order By: Relevance
“…rotundata Bliding from Southern Spain. At the natural site, the top layer of these mat-like canopies is generally completely bleached, but acts as a selective UV-B Wlter, and thus prevents subcanopy thalli from exposure to harmful radiation (Bischof et al 2002). Cells and tissue of brown algae that contain UV-absorbing compounds have the potential to protect any underlying living cells from the harmful eVect of high levels of UVR.…”
Section: Discussionmentioning
confidence: 99%
“…rotundata Bliding from Southern Spain. At the natural site, the top layer of these mat-like canopies is generally completely bleached, but acts as a selective UV-B Wlter, and thus prevents subcanopy thalli from exposure to harmful radiation (Bischof et al 2002). Cells and tissue of brown algae that contain UV-absorbing compounds have the potential to protect any underlying living cells from the harmful eVect of high levels of UVR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the importance of canopy arrangement for maintaining high production rates of algal assemblages within these highly eutrophic systems (Pérez-Lloréns et al, 1996;Hernández et al, 1997). A recent study on the effects of solar UV radiation on Ulva canopies proposed canopy formation as an ecological strategy for shielding productive material from harmful UV-B radiation (Bischof et al, 2002b): the bleached top layers of mats, which exhibit marked absorption of solar radiation only in the UV-B range of the spectrum, shield the subcanopy layers. In the same study it was also proposed that under field conditions the combination of high irradiance of photosynthetically active radiation (PAR) and UV-B radiation results in the loss of photosynthetic proteins and pigments, probably due to a high production of reactive oxygen species (ROS) in photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…the top layer of the mat-like canopies is generally completely bleached thereby providing photoprotection for subcanopy thalli (Bischof et al, 2002).…”
mentioning
confidence: 99%